2019
DOI: 10.7196/samj.2019.v109i11.14017
|View full text |Cite
|
Sign up to set email alerts
|

Closed traction reduction of cervical spine facet dislocations: Compelled by law

Abstract: The urgency of closed reduction of acute low-velocity cervical facet dislocations has recently been highlighted by the Constitutional Court of South Africa (SA), following a permanent spinal cord injury that a young rugby player sustained during a club-level match. The court found that if emergency care of the complainant had resulted in rapid closed reduction of his cervical spine injury, he might not have suffered permanent neurological damage. [1] The findings of the court were based on research by Newton e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 22 publications
(33 reference statements)
0
2
0
Order By: Relevance
“…8 A retrospective review of rugby players with cervical dislocations found a 63% difference in reported neurological improvement if closed reduction was performed within four hours of the injury -a larger quantified effect on patient recovery than surgical intervention. 9 All Western Cape hospitals strive to perform closed reduction of cervical dislocations within four hours of the injury, 10 partly to comply with a 2015 Constitutional Court ruling but also to adhere to best medical practice. 11 This is, however, particularly challenging as the mean transport time between sustaining a spinal injury and receiving medical care was previously found to be three hours, which leaves little room to comply with the four-hour ruling.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…8 A retrospective review of rugby players with cervical dislocations found a 63% difference in reported neurological improvement if closed reduction was performed within four hours of the injury -a larger quantified effect on patient recovery than surgical intervention. 9 All Western Cape hospitals strive to perform closed reduction of cervical dislocations within four hours of the injury, 10 partly to comply with a 2015 Constitutional Court ruling but also to adhere to best medical practice. 11 This is, however, particularly challenging as the mean transport time between sustaining a spinal injury and receiving medical care was previously found to be three hours, which leaves little room to comply with the four-hour ruling.…”
Section: Introductionmentioning
confidence: 99%
“…11 This is, however, particularly challenging as the mean transport time between sustaining a spinal injury and receiving medical care was previously found to be three hours, which leaves little room to comply with the four-hour ruling. 10 Therefore, a new management protocol was introduced in June 2016 -the 'early reduction protocol' -requiring all closed reductions to be performed within one hour of admission.…”
Section: Introductionmentioning
confidence: 99%